2020
DOI: 10.3389/fphys.2020.00902
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Resuscitation of Asystolic Newborn Lambs Prior to Umbilical Cord Clamping; the Timing of Cord Clamping Matters!

Abstract: Background: Current guidelines recommend immediate umbilical cord clamping (UCC) for newborns requiring chest compressions (CCs). Physiological-based cord clamping (PBCC), defined as delaying UCC until after lung aeration, has advantages over immediate UCC in mildly asphyxiated newborns, but its efficacy in asystolic newborns requiring CC is unknown. The aim of this study was to compare the cardiovascular response to CCs given prior to or after UCC in asystolic near-term lambs. Methods: Umbilical, carotid, pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 48 publications
1
34
0
7
Order By: Relevance
“…DCC for 15 min restored cardiac output and oxygenation and mitigated post-asphyxial rebound hypertension after resuscitation in a non-arrest ovine model of perinatal asphyxia induced by maternal iliac artery ligation [ 13 ]. In lambs with asphyxial arrest, DCC for 10 min caused significant reductions in post-asphyxial rebound hypertension, cerebral blood flow and oxygenation [ 20 ]. These studies indicate improved hemodynamics with a longer DCC duration, and along with a difference in methodology of induced asphyxia (cord occlusion vs. maternal iliac artery ligation), may explain lack of sustained benefits in our study.…”
Section: Discussionmentioning
confidence: 99%
“…DCC for 15 min restored cardiac output and oxygenation and mitigated post-asphyxial rebound hypertension after resuscitation in a non-arrest ovine model of perinatal asphyxia induced by maternal iliac artery ligation [ 13 ]. In lambs with asphyxial arrest, DCC for 10 min caused significant reductions in post-asphyxial rebound hypertension, cerebral blood flow and oxygenation [ 20 ]. These studies indicate improved hemodynamics with a longer DCC duration, and along with a difference in methodology of induced asphyxia (cord occlusion vs. maternal iliac artery ligation), may explain lack of sustained benefits in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant Border-Leicester ewes ( Ovis aries ) at 139±2 days’ gestation (term ~148 days) were anaesthetised by intravenous injection of thiopentone sodium (20 mg/kg; Jurox, NSW, Australia), followed by tracheal intubation and delivery of inhaled anaesthesia (isofluorane 1.5%–2.5% in oxygenated air; Bomac Animal Health, NSW, Australia). Fetal surgery and instrumentation have been described in detail previously 10 12. Briefly, ultrasonic flow transducers (Transonic Systems, Ithaca, NY, USA) were placed around the left main pulmonary artery and left carotid artery, and catheters were inserted into a carotid artery and jugular vein 10 12 13.…”
Section: Methodsmentioning
confidence: 99%
“…Fetal surgery and instrumentation have been described in detail previously 10 12. Briefly, ultrasonic flow transducers (Transonic Systems, Ithaca, NY, USA) were placed around the left main pulmonary artery and left carotid artery, and catheters were inserted into a carotid artery and jugular vein 10 12 13. Arterial pressures and blood flows were digitally recorded in real time (1 kHz, Powerlab; ADInstruments, NSW, Australia) 10.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach would be to perform resuscitation while the cord is still intact. Several studies have demonstrated improvements in physiological outcomes, such as higher Apgar scores or oxygen levels in the first few minutes of birth with resuscitation with an intact cord compared to early cord clamping [ 6 , 7 , 8 , 9 , 10 , 11 ]. Another challenge, however, is implementation of this practice.…”
mentioning
confidence: 99%